P56 Comparison of the first 650 and the latest 524 laparoscopic transperitoneal pelvic/paraaortic lymphadenectomies in a series of 2535 patients treated for different gynaecological cancers. (1st November 2019) - Jacob, A; Plaikner, A; Mallmann, P; Di Favero, G; Tozzi, R; Martus, P; Marnitz, S; Köhler, C
Abstract : Introduction/Background: Lymphadenectomy is an integral part of operative staging and treatment of gynaecological malignancies. Since its introduction over 25 years ago, laparoscopic lymphadenectomy has proven to be feasible, safe and oncologically adequate in comparison to open surgery while morbidity is lower and hospital stay is considerably shorter. Methodology: In this retrospective study we analysed our prospectively collected data of laparoscopic pelvic and/or paraaortic lymphadenectomies performed between 1994 and 2018 by one team of gynaecological oncology surgeons. Data was analysed with regards to operation time, intra- and postoperative complications, number of harvested lymph nodes and influence of BMI. Previously published data of the first 650 patients treated after introduction of the method between 1994 and 2003 (period 1) was compared with the data of the latest 524 patients treated between 2014 and 2018 (period 2). Results: Indications for pelvic and/or paraaortic lymphadenectomies in the 2535 patients were cervical cancer, endometrial cancer, vulvar cancer with positive groin nodes, early ovarian cancer, vaginal cancer, uterine carcinosarcoma and others in a number of 1893, 361, 62, 99, 28, 13 and 79 patients, respectively. The learning curve for the two procedures was already completed during the first 650 cases. Since 1999 a steady and oncologically adequate number of lymph nodes were harvested in both areas independent of patients' BMI. OR-time for paraaortic lymph node dissection was shorter in period 2 (69 vs 100 min). In contrast to period 1 (2.9%), there were no intraoperative complications in period 2, whereas postoperative complications are similarly frequent (5.8 vs 7.6%). Conclusion: In this large cohort of patients who underwent laparoscopic lymphadenectomy the oncological equivalency and minimal morbidity of this approach was once again demonstrated. With growing experience intraoperative complication rates can be minimised. Teaching and integration of new team members does not impair surgical results when performed under supervision. Disclosure: Nothing to disclose.